2011
DOI: 10.1177/1368430210392932
|View full text |Cite
|
Sign up to set email alerts
|

Ingroup identification as a moderator of racial bias in a shoot–no shoot decision task

Abstract: At least since the 1999 Bronx shooting (Fritsch, 2000) of unarmed Amadou Diallo by New York City police officers, social psychologists have had an interest in the dynamics of decisions to shoot or not shoot potentially dangerous suspects. Of key theoretical interest in subsequent research has been the confluence of split-second decisionmaking and the effects of racial stereotypes on response bias against Black targets. Our aim in this article is to replicate and extend prior research on this topic by testing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…An overall score was calculated for each participant by summing all o f the item scores. A higher score indicates a greater sense o f identification with racial in-groups Kenworthy et al (2011). found the reliability o f this scale to be excellent (a = .94) and a similarly strong reliability score was found in this study (a = .92).…”
supporting
confidence: 82%
See 3 more Smart Citations
“…An overall score was calculated for each participant by summing all o f the item scores. A higher score indicates a greater sense o f identification with racial in-groups Kenworthy et al (2011). found the reliability o f this scale to be excellent (a = .94) and a similarly strong reliability score was found in this study (a = .92).…”
supporting
confidence: 82%
“…Continuing in the effort to understand Black-White biases in shooting decisions, Kenworthy, Barden, Diamond, and del Carmen (2011) Using signal detection analysis to examine their results they found that c varied significantly as a function of in-group identification, such that those participants who were higher on an in-group identification questionnaire exhibited a larger shoot-bias (i.e., a lower c) when encountering Black targets.…”
Section: Stereotypes and Shooting Behaviourmentioning
confidence: 99%
See 2 more Smart Citations
“…Under threatening circumstances, in-group identifiers do tend to engage in greater prejudice and discrimination (Branscombe & Wann, 1994;Brown, Maras, Masser, Vivian, & Hewstone, 2001;Duckitt & Mphuthing, 1998;Grant & Brown, 1995;Kenworthy, Barden, Diamond & del Carmen, 2011;Lowery et al, 2006;Perreault & Bourhis, 1999;Riek, Mania & Gaertner, 2006;Stephan et al, 2002;Stephan, Ybarra, Martinez, Schwarzwald, & Tur-Kaspa, 1998;Struch & Schwartz, 1989;Voci, 2006), despite the lack of a reliable, cross-situation correlation between in-group identification and out-group antipathy (Brewer & Campbell, 1976;Brown, 2000;Hinkle & Brown, 1990). For example, in field studies among different ethnic groups, in-group identification predicts out-group prejudice only among groups with a history of conflict and oppression (Bombay, Matheson, & Anisman, 2010;Brewer & Campbell, 1976;Duckitt, Callaghan, & Wagner, 2005;Hinkle & Brown, 1990).…”
Section: Situational Threat In Negotiationmentioning
confidence: 99%